Drugs that Affect Platelet Function - Scharf, Rüdiger E. (Seminars in Thrombosis and Hemostasis, 2012)
Drugs represent the most common cause of platelet dysfunction in our overmedicated society. While acetylsalicylic acid (aspirin), adenosine diphosphate receptor antagonists (clopidogrel and prasugrel), and integrin αIIbβ3 (GPIIb-IIIa) receptor blockers (abciximab, eptifibatide, and tirofiban) are well-known prototypes of antiplatelet drugs, other widely used agents such as nonsteroidal anti-inflammatory drugs, antibiotics, cardiovascular and lipid-lowering drugs, selective serotonin reuptake inhibitors, and volume expanders can also impair platelet function and thus cause or aggravate hemorrhages in certain clinical settings. Therefore, induction of a bleeding diathesis remains a significant concern. This is especially relevant in patients with preexisting hemostatic defects of any kind, which may remain compensated as long as platelet function (and/or coagulation) is not inhibited pharmacologically. Identification of individual patients with preexisting hemostatic defects remains crucial (1) to prevent otherwise unexpected bleeding complications, (2) to manage hemorrhagic symptoms adequately, (3) to minimize the risk from invasive procedures, and (4) to avoid unnecessary patient exposure to blood products. This article provides a review of the large variety of agents that have not been designed for antiplatelet therapy but nevertheless interfere with platelet reactivity or induce platelet inhibition. In particular, drug interactions and mechanisms by which these agents can trigger or cause platelet dysfunction are detailed.
Keywords: nonsteroidal anti-inflammatory drugs (NSAIDs); antibiotics; cardiovascular and lipid-lowering drugs; psychotropic agents; drug interactions